2002
DOI: 10.1074/jbc.m109945200
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of Surface Proteins to the Cell Wall of Staphylococcus aureus

Abstract: Surface proteins of Staphylococcus aureus are anchored to the cell wall peptidoglycan by a mechanism requiring a C-terminal sorting signal with a LPXTG motif. Sortase cleaves polypeptides between the threonine and the glycine of the LPXTG motif. The carboxyl group of threonine is subsequently amide-linked to the amino group of peptidoglycan cross-bridges. The three-dimensional structure of sortase revealed the close proximity of the catalytic site residue cysteine 184 with histidine 120; however, no structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
108
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 29 publications
4
108
0
2
Order By: Relevance
“…The initial steps in the transpeptidation reaction include the cleavage of the scissile bond of a substrate and the formation of an acyl-enzyme intermediate, steps that are very similar to those seen in reactions catalyzed by all cysteine proteases (6,30). Comparison of SrtA with other cysteine proteases would benefit our understanding of the mechanism of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial steps in the transpeptidation reaction include the cleavage of the scissile bond of a substrate and the formation of an acyl-enzyme intermediate, steps that are very similar to those seen in reactions catalyzed by all cysteine proteases (6,30). Comparison of SrtA with other cysteine proteases would benefit our understanding of the mechanism of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Previous determination of the three-dimensional structure of SrtA ⌬N59 using NMR revealed three residues, Cys 184 together with His 120 and Asn 98 , arranged in a disposition similar to that of the catalytic triad observed in classic cysteine proteases such as papain (31). Because a thiolate-imidazolium ion pair is structurally and functionally conserved among the superfamily of cysteine proteases, proximally positioned Cys 184 and His 120 residues in SrtA were thought to act as the catalytic ion pair (30,31). However, the thiol group of Cys 184 was seen pointing away from the imidazole ring of His 120 and the distance between the two side chains was much farther than that observed in a typical catalytic cysteine-histidine ion pair.…”
mentioning
confidence: 99%
“…Different functions have also been proposed for His 120 . Originally, it was suggested that it activated Cys 184 by forming an imidazolium-thiolate ion pair (26). However, subsequent pK a measurements revealed that both His 120 and Cys 184 are predominantly uncharged at physiological pH values, leading to the suggestion that His 120 functions as a general base during catalysis (33).…”
mentioning
confidence: 99%
“…Both the hydrophobic domain and the charged tail help to retain the putative surface protein in the membrane prior to sortase-catalyzed anchoring. SrtA cleaves the LPXTG sequence between the threonine and glycine residues by use of a nucleophilic active site cysteine (Cys 184 ) (20). An acyl-enzyme intermediate is formed, which is then resolved by nucleophilic attack from an amino group on the Gly 5 cross-bridge of branched Lipid II.…”
mentioning
confidence: 99%